Scalable nanoporous carbon films allow line-of-sight 3D atomic layer deposition of Pt: towards a new generation catalyst layer for PEM fuel cells. Issue 9 (20th August 2021) - Atwa, Marwa; Li, Xiaoan; Wang, Zhaoxuan; Dull, Samuel; Xu, Shicheng; Tong, Xia; Tang, Rui; Nishihara, Hirotomo; Prinz, Fritz; Birss, Viola
Abstract : A self-supported, binder-free and scalable nanoporous carbon scaffold serves as an excellent host for the efficient and uniform atomic layer deposition of Pt nanoparticles, showing exemplary performance as a cathode catalyst layer in a PEM fuel cell. Abstract : Although nanoporous carbons are ubiquitous materials that are used in many clean energy and environmental applications, most are in powder form, thus requiring binders to hold particles together. This results in uncontrolled and complex pathways between particles, potentially exacerbating mass transport issues. To overcome these problems, we have developed an unprecedented binderless, self-supported, nanoporous carbon scaffold (NCS) with tunable and monodisperse pores (5–100+ nm), high surface area ( ca. 200–575 m 2 g −1 ), and 3-dimensional scalability (1–150+ cm 2, 1–1000 μm thickness). Here, it is shown that NCS85 membranes (85 nm pores) are particularly promising as a host for the homogeneous and efficient 3-D atomic layer deposition (ALD) of Pt nanoparticles, due to the facile penetration of gas phase Pt precursor throughout the homogeneous, low tortuosity internal structure. Furthermore, the high density of surface defects of the as-synthesized NCS promotes uniform Pt nucleation with minimal agglomeration. These advantageous features are key to the rapid oxygen reduction kinetics observed under polymer electrolyte membrane (PEM) fuel cell MEA testing conditions. Cells constructed with an optimal ALD Pt loading of 30 cycles are shown to exhibit a specific activity of ≥0.4 mA cm −2 Pt which is exemplary when compared to two commercial catalyst layers with comparable Pt mass loadings and tested under the same conditions. Furthermore, a maximum power density of 1230 mW cm −2 (IR-corrected) is obtained, with the limiting current densities approaching a very respectable 3 A cm −2 .